Rehabilitation Approaches for Knee Arthroplasty - Roza V. Petrova; Nikolay S. Nikolaev; Mikhail B. Tsykunov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Up to 25% of patients after knee arthroplasty are not satisfied with the results of the operation. Revision interventions are performed in60-80% of cases in the first 2-5 years after the primary arthroplasty.Aim. To evaluate the effectiveness of the early postoperative rehabilitation comprehensive program from the standpoint of the InternationalClassification of Functioning (ICF) to improve the results of rehabilitation after arthroplasty.Material and methods. The results of 180 patients rehabilitation after the total knee arthroplasty (TKA) with simultaneous reconstructionof the lower limb biological axis were evaluated in two groups: I - observations (n=120), II - comparisons (n=60). Postoperativerehabilitation in the group I was carried out according to of the early rehabilitation comprehensive program after TKA, developed inthe clinic, in the group II - according to the standard scheme. State of the patient was assessed by the dynamics of the pain syndrome,lower limbs muscle strength, goniometric indicators, the severity of lameness, muscle hypotrophy, limb shortening value, functionalactivity and quality of life. For analysis of changes in the level of damage according to the ICF, clinical tests were used.Results. From the standpoint of the ICF, the results of patients using the early postoperative rehabilitation program were equal or superiorto the results of the comparison group.Conclusion. A rehabilitation program for patients after TKA, formed on the basis of a system for assessing the structural, functional andsocial adaptation characteristics of the patient, is effective and allows to predict the effectiveness of the rehabilitation technologies.